2021
DOI: 10.1111/jhn.12944
|View full text |Cite
|
Sign up to set email alerts
|

Culinary medicine and culinary nutrition education for individuals with the capacity to influence health related behaviour change: A scoping review

Abstract: Background Culinary medicine (CM) or culinary nutrition (CN) education provided to professionals with the capacity to influence behaviour change is an emerging strategy to promote diet quality and reduce the burden of diet related chronic disease in adults. The purpose of this scoping review was to synthesise current research describing CM/CN education provided to or by health, education and culinary professionals, or students of these disciplines. Methods Preferred Reporting Items for Systematic reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 52 publications
(285 reference statements)
2
40
0
Order By: Relevance
“…Reasons for excluding articles reviewed as full-text included wrong study design ( n = 13) [ 4 , 12 – 23 ], wrong population ( n = 5) [ 24 28 ], a failure to report any outcome measures ( n = 3) [ 9 , 29 , 30 ], wrong intervention ( n = 3) [ 26 , 31 , 32 ], and five studies were found to be duplicates of an included paper or had used the same data ( n = 5) [ 33 37 ]. Amongst the 24 included studies, there were six qualitative studies [ 38 43 ], four cross-sectional studies [ 34 , 44 46 ]; seven case studies [ 47 – 53 ], and seven mixed-methods study [ 35 , 54 – 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for excluding articles reviewed as full-text included wrong study design ( n = 13) [ 4 , 12 – 23 ], wrong population ( n = 5) [ 24 28 ], a failure to report any outcome measures ( n = 3) [ 9 , 29 , 30 ], wrong intervention ( n = 3) [ 26 , 31 , 32 ], and five studies were found to be duplicates of an included paper or had used the same data ( n = 5) [ 33 37 ]. Amongst the 24 included studies, there were six qualitative studies [ 38 43 ], four cross-sectional studies [ 34 , 44 46 ]; seven case studies [ 47 – 53 ], and seven mixed-methods study [ 35 , 54 – 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study is one of the first reviews, along with Patel & Kassam 2021 and Asher et al 2022, to advance understanding of current opportunities and obstacles for culinary medicine within the context of medical, or other health care professional education, by examining the impact of culinary medicine in medical programs using a systematic approach [ 4 , 18 ]. In recent years, a clear interest in the use of culinary medicine as an education tool has been demonstrated in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying the overall goals, objectives, and vision of a CM/CN program is an important step to help guide your approach. For example, if your purpose is to carry out a health intervention using a teaching kitchen, choosing what you hope to change and how the program can support this can be helpful in promoting behavior change (Rigby et al 2020;Asher et al 2021). This was applied in a virtual CM program (five 90-minute sessions) among patients with type 2 diabetes that specified program inputs (like materials and training), change objectives (like culinary skills), and desired outcomes (including healthy eating and food practices, better access to food, and improvements in disease risk factors) (Sharma et al 2021).…”
Section: First Steps: Food For Thoughtmentioning
confidence: 99%